2020
DOI: 10.3382/ps/pez570
|View full text |Cite
|
Sign up to set email alerts
|

Proper cold stimulation starting at an earlier age can enhance immunity and improve adaptability to cold stress in broilers

Abstract: The effects of long-term cold stimulation on the immune function of ileum and adaptability to cold stress in broilers were examined. A total of 360 Arbor Acres broilers was divided into 3 groups and four replicates per group. C (control) was reared in normal thermal environment. C-3 and C-12 (treatments) were kept in cold condition of 3 or 12°C lower than the temperature of C from days 8 to 42. At day 42, all the groups were exposed to an acute cold stress challenge, designated as S, S-3, and S-12. The mRNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
1
27
0
1
Order By: Relevance
“…Acute change in environmental temperature may have negative impacts on the performance of broiler flocks. It has been observed that a severe cold stress (12°C below the homeostatic temperature) throughout the life cycle of broilers negatively impacted production parameters ( Su et al., 2020 ). Besides the negative effects on the performance of the birds, cold stress can also impair immune system development ( Zhang et al., 2011 ; Zhao et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute change in environmental temperature may have negative impacts on the performance of broiler flocks. It has been observed that a severe cold stress (12°C below the homeostatic temperature) throughout the life cycle of broilers negatively impacted production parameters ( Su et al., 2020 ). Besides the negative effects on the performance of the birds, cold stress can also impair immune system development ( Zhang et al., 2011 ; Zhao et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [ 10 ] showed that the expression levels of IgA and IgG had an increased tendency in acute and chronic cold stress. Su et al [ 14 , 18 ] suggested that long-term and sustained cold stimulation increase the gene levels of immunoglobulin in ileum of broilers. Similar to previous studies, our results show a gradual increasing tendency in mRNA levels of IgA and IgG in the small intestine of broilers submitted to intermittent mild cold stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, secretory IgA produced in the lamina propria is a vital protective molecule for the intestinal epithelium [ 13 ]. Moreover, proper cold stimulation has been shown to increase the expression of intestinal IgA and IgG to resist adverse effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В литературе описано угнетающее действие радиоактивного излучения на все элементы стенки трахеи (7) и отрицательное влияние углекислого газа, приводящее к отекам слизистой (2). В ряде работ отмечено влияние низких температур на анатомо-гистологическое строение трахеи (4,18,19).…”
unclassified